Analysis of Factors For Increasing Income Tax in Motor Vehicles in UPT PPD (Technical Implementing Unit of Regional Revenue Management) in Siantar - Dona Hendrianto Damanik; Marlon Sihombing; Hamdani Harahap (Budapest International Research and Critics University, 2021)
In principle, motor vehicle tax plays a role in providing PAD for the North Sumatra Provincial Government. In this connection, the tax target must be increased every year and contribute to development in North Sumatra. To optimize the potential for motor vehicle tax revenue, it is necessary to know the factorsin increasing motor vehicle tax revenue at the UPT PPD (Technical Implementation Unit for Regional Revenue Management). ThereforeThe formulation of the problem in this study is as follows: